الانستغرام و علاقته بالترويج للمنسوجات التقليدية بالاغواط - كوثر بوقناشة; روميسا قاسمي (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة : هدفت الدراسة إلى التعرف على الأنستغرام و ما علاقته بالترويج لمنسوجات التقليدية بالاغواط (دراسة حالة بغرفة الصناعة التقليدية بالاغواط) و مدى نجاح استراتيجية الترويج المنسوجات التقليدية عبر الانستغرام حيث تم استخدام المنهج الوصفي التحليلي و تكونت عينة الدراسة من 30 مرأة حرفية و طبقنا الإستبيان عليهم و و توصلت الدراسة إلى النتاىج التالية: • يعتمد أصحاب المنسوجات التقليدية في تسويق منسوجاتهم عبر الأنستغرام بشكل قوي. • للأستغرام دور كبير نحو اقبال الافراد عل استخدام المنسوجات التقليدية كبديل لمنسوجات الصناعية الحديثة. • إن استخدام مواقع التواصل الاجتماعي عامة و الانستغرام خاصة كأداة في تفعيل الانشطة الحرفية النسوية و لترويج و تسويق منسوجات الصناعة التقليدية و الحرف. الكلمات المفتاحية : الإنستغرام– مواقع التواصل الاجتماعي – الترويج-المنسوجات التقليدية Abstract The study aimed to investigate the relationship between Instagram and the promotion of traditional textiles in El-Oued (a case study with the Traditional Industry Chamber in El-Oued), and the extent of success of the strategy of promoting traditional textiles through Instagram. The descriptive analytical method was used, and the study sample consisted of 30 craftswomen who were surveyed. The study reached the following conclusions: Owners of traditional textiles rely heavily on marketing their products through Instagram. Instagram plays a significant role in people's inclination towards using traditional textiles as an alternative to modern industrial textiles. The use of social media platforms, particularly Instagram, serves as a tool for activating female craft activities and for promoting and marketing traditional industrial textiles and crafts keywords : Instagram - Social media sites – Promotion- Traditional textiles.
دراسة استطلاعية على عينة من حرفيات بغرفة الصناعة التقليديةو الحرف بالاغواط